Spermatic cord anastomosing hemangioma mimicking a malignant inguinal tumor: A case report and literature review - Zhang, Zhan-yi; Hong, Peng; Deng, Shao-hui; Tang, Shi-ying; Liu, Zhuo; He, Hui-ying; Ma, Lu-lin; Zhang, Shu-dong; Tian, Xiao-jun (Frontiers in Surgery, 2022)
Background Anastomosing hemangioma (AH) is a rare vascular tumor and occurs in various organs. It is difficult to distinguish AH from malignant tumors even through multimodal imaging examination. AH located in the inguinal region is even rare. We present the diagnosis and treatment of a patient with spermatic cord AH in detail and conduct a literature review. Case Report An 84-year-old Chinese man had swelling pain in his right scrotum. A hard and fixed mass was palpable in the right inguinal region. Preoperative radiological examination considered it a neurogenic or vascular tumor. Malignant soft tissue sarcoma could not be excluded. He underwent radical inguinal right orchiectomy under intraspinal anesthesia. The diagnosis of spermatic cord AH was confirmed by pathological examination. The patient recovered uneventfully and remained disease-free during an 18-month follow-up. Conclusion Spermatic cord AH is quite rare and could be misdiagnosed as a malignant tumor. Pathological evidence might be necessary. The optimal choice of treatment should be determined through a comprehensive assessment of both tumor and patient factors.